Cytogenetic Analysis After Temporary Residence in the Area of the Uncontrolled Ruthenium-106 Release in Russia in September 2017. Issue 6 (December 2019) - Beinke, C.; Wanke, C.; Eder, S.; Port, M.
Abstract : Abstract: In September and October 2017, elevated atmospheric ruthenium contamination was measured in several European countries. The most probable origin of this release of radionuclides was reconstructed to be the Southern Ural region. During that time, five workers from a German company stayed up to 2 wk about 120 km from the Chelyabinsk region in Ekaterinburg, Russia. No clinical symptoms were reported during or after the suspected radiation exposure, and no internal contamination was found in whole-body measurements. However, to investigate radiation protection issues and to clarify the workers' situation in order to reassure them, as they planned to continue working in Ekaterinburg, our laboratory was urgently requested by the company's occupational physician to perform biodosimetry using dicentric analysis to determine if the workers have been exposed to radiation by incorporation of radionuclides. The workers' dicentric yields have been compared to reference data of background frequencies in unexposed individuals, but, as it is not reasonable to quantify individual absorbed radiation doses from internalized beta emitters due to various confounding factors, individual dose estimation has not been performed. Dicentric frequencies for two workers differed significantly from the mean laboratory background level, which could have been induced by an exposure to incorporated radionuclides due to beta emissions by 106 Ru or to gamma irradiation by the decay nuclide of 106 Ru. However, the maximum absorbed radiation doses calculated for a resident in the 106 Ru-contaminated area during that time does not correspond to the observed dicentric frequencies. It cannot be excluded that their dicentric frequencies were already elevated before September 2017, potentially induced by an earlier radiation exposure to diagnostic x rays or even by chance.